Frederick Douglass : a noble life - Adler, David A. (Holiday House, 2010)
When, in 1879, a bust in his likeness was placed at the University of Rochester, Frederick Douglass wrote: "Incidents of this character do much amaze me. It is not, however, the height to which I have risen, but the depth from which I have come that amazes me." This biography tells the story of his ascent from slavery.